Advertisement Remove all ads

Solve the Following Equation For X: `2^(X+1)=4^(X-3)` - Mathematics

Solve the following equation for x:

`2^(x+1)=4^(x-3)`

Advertisement Remove all ads

Solution

`2^(x+1)=4^(x-3)`

`rArr2^(x+1)=(2^2)^(x-3)`

`rArr2^(x+1)=(2^(2x-6))`

⇒ x + 1 = 2x - 6

⇒ 2x - x = 1 + 6

⇒ x = 7

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 2 Exponents of Real Numbers
Exercise 2.1 | Q 8.2 | Page 12
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×